Penerapan Penanggulangan Sampah Di Batu Besar - Mada Surya Darmawan; Kelvin Kelvin; Yuliana Yuliana; Santy Santy; Muhammad Faiq Renaldy Andadinata; Mentari Deseka; Oda L.B. Haryanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
Garbage is a part of human life. Garbage is an object/waste that is not used. Garbage should receive serious attention and handling. However, due to the lack of understanding of the community and the government, as well as the lack of cost and income of the majority of the community, this waste problem has become neglected. At present most of the people have learned about the adverse effects of waste, including causing floods, diseases, and odors that can interfere with life, but this is not balanced by the behavior of the community itself so the purpose of writing the article is as a form of community service by inviting the community in Kampung Melayu RW.02, Batu Besar Village, Nongsa District on how to deal with both organic and inorganic waste by providing trash bins, providing socialization and modules in socialization activities